Aplikasi Buju Saku English for Tourism Bagi Kelompok Sadar Wisata Batu Kijuk Kecamatan Sekotong Kabupaten Lombok Barat - Arafiq, Arafiq; Ahmadi, Nur; Aziz, Atri Dewi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Sekotong is one of the important destinations in Lombok which is frequently visited by local and foreign tourists. Considering this presence of these tourists, the community who live Sekotong can start up new business fields, for instance accommodation, food and beverage, and tour guide services, and transports for the tourists who visit the small islands located in Sekotong. This Community Service aims to provide Practical English Conversation Application Assistance for Local Guides and boatmen in Sekotong District, Lombok Regency including conversations about Welcome Tourists, Introducing to Tours, Explaining Safety, Rules, Etiquette, Showing Places of Interest, aspects of Tour vocabulary Guide Vocabulary, and examples of Tour Guide Speech recordings. This Community Service was carried out using a participatory method so that all participants could get involved in the learning, from planning, implementation, to the evaluation stage. This community service has brought positive effect, especially to boatmen and all participants in general. They have shown better English skills than before. It is hoped that the boatmen will become more confident in using English skills when dealing with foreign tourists.